1987
DOI: 10.1007/bf00750732
|View full text |Cite
|
Sign up to set email alerts
|

Keratin immunohistochemistry in normal human liver. Cytokeratin pattern of hepatocytes, bile ducts and acinar gradient

Abstract: A panel of 2 polyclonal and 7 monoclonal antibodies directed against cytokeratins was tested on cryostat and paraffin sections of 14 normal human liver biopsies using an immunoperoxidase procedure. The staining characteristics of hepatocytes and bile ducts are reported. On cryostat sections, monoclonal antibodies directed against individual cytokeratins no. 8 and no. 18 stained both bile ducts and hepatocytes, whereas monoclonals anti-cytokeratin no. 7 and no. 19 exclusively stained bile ducts. The potential u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(62 citation statements)
references
References 21 publications
2
59
0
1
Order By: Relevance
“…Although oval cells are thought to emanate from the periportal area [4][5][6][7][8], their lineage remains controversial. Immunofluorescence studies revealed that oval cells express cytokeratin 19 (CK19), a marker specific for the biliary tree that includes bile ducts as well as the canal of Hering [8,9]. OV6, the most widely used monoclonal antibody to identify oval cells in rat liver [10], stains similar structures [11], indicating that epithelial cells residing within the canal of Hering are the most probable candidates for resident liver stem cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although oval cells are thought to emanate from the periportal area [4][5][6][7][8], their lineage remains controversial. Immunofluorescence studies revealed that oval cells express cytokeratin 19 (CK19), a marker specific for the biliary tree that includes bile ducts as well as the canal of Hering [8,9]. OV6, the most widely used monoclonal antibody to identify oval cells in rat liver [10], stains similar structures [11], indicating that epithelial cells residing within the canal of Hering are the most probable candidates for resident liver stem cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…We have compared the pattern of OV-6 expression with two known biliary cell markers, human epithelial antigen-125 (HEA-125) and the intermediate filament cytokeratin . [20][21][22][23] …”
mentioning
confidence: 99%
“…Inc., (San Mateo, CA, USA). Monoclonal antibodies (KL-1 and CAM) against cytokeratin are known to stain hepatocytes as well as biliary epithelial cells in man (Van Eyken et al 1987).…”
Section: Methodsmentioning
confidence: 99%